Heart failure with preserved ejection fraction: New approaches to diagnosis and management - Upadhya, Bharathi; Kitzman, Dalane W. (Clinical cardiology (Mahwah, N.J.), 2020)
The majority of older patients who develop heart failure (HF), particularly older women, have a preserved left ventricular ejection fraction (HFpEF). Patients with HFpEF have severe symptoms of exercise intolerance, poor quality‐of‐life, frequent hospitalizations, and increased mortality. The prevalence of HFpEF is increasing and its prognosis is worsening. However, despite its importance, our understanding of the pathophysiology of HFpEF is incomplete, and drug development has proved immensely challenging. Currently, there are no universally accepted therapies that alter the clinical course of HFpEF. Originally viewed as a disorder due solely to abnormalities in left ventricular (LV) diastolic function, our understanding has evolved such that HFpEF is now understood as a systemic syndrome, involving multiple organ systems, likely triggered by inflammation and with an important contribution of aging, lifestyle factors, genetic predisposition, and multiple‐comorbidities, features that are typical of a geriatric syndrome. HFpEF is usually progressive due to complex mechanisms of systemic and cardiac adaptation that vary over time, particularly with aging. In this review, we examine evolving data regarding HFpEF that may help explain past challenges and provide future directions to care patients with this highly prevalent, heterogeneous clinical syndrome.